Postoperative changes in the pharyngeal airway space through computed tomography evaluation after mandibular setback surgery in skeletal class III patients: 1-year follow-up - No Eul Kang; Dae Hun Lee; Ja In Seo; Jeong Keun Lee; Seung Il Song (SpringerOpen, 2021)
Abstract Background This study evaluated the pharyngeal airway space changes up to 1 year after bilateral sagittal split osteotomy mandibular setback surgery and bimaxillary surgery with maxillary posterior impaction through three-dimensional computed tomography analysis. Methods A total of 37 patients diagnosed with skeletal class III malocclusion underwent bilateral sagittal split osteotomy setback surgery only (group 1, n = 23) or bimaxillary surgery with posterior impaction (group 2, n = 14). Cone-beam computed tomography scans were taken before surgery (T0), 2 months after surgery (T1), 6 months after surgery (T2), and 1 year after surgery (T3). The nasopharynx (Nph), oropharynx (Oph), hypopharynx (Hph) volume, and anteroposterior distance were measured through the InVivo Dental Application version 5. Results In group 1, Oph AP, Oph volume, Hph volume, and whole pharynx volume were significantly decreased after the surgery (T1) and maintained. In group 2, Oph volume and whole pharynx volume were decreased (T2) and relapsed at 1 year postoperatively (T3). Conclusion In class III malocclusion patients, mandibular setback surgery only showed a greater reduction in pharyngeal airway than bimaxillary surgery at 1 year postoperatively, and bimaxillary surgery was more stable in terms of airway. Therefore, it is important to evaluate the airway before surgery and include it in the surgical plan.